Illustrating the past, present and future perspective of Human Embryo Culture Media - Saugandhika, Shrabani; Sharma , Vishal; Khatak, Kamini (Animal Reproduction Update, 2022)
Culture media has an important role in invitro embryo development and in determining the success rate of assisted reproduction technologies. Extensive research during the last few decades have brought about major advancements in the IVF culture media. Studies on the composition of the mammlian oviductal fluids and the uterine fluids have improved our understanding on the evolving metabolic needs of the preimplantation embryo. This  has led to the gradual development of human IVF media, from simple salt solutions to highly complex defined media. Regarding ideal composition of IVF culture media two different philosophies have come up: “back-to-nature” or sequential culture principle and “let-the-embryo-choose” or one-step culture principle.  Sequential culture closely mimics the physiological conditions of female reproductive tract, while the mono culture system employs simultaneous use of all components in an optimal concentration. Besides role in viability maintenance, culture media can also take up a new role as a therapeutic agent in future. The improvised media apart from maintaining the viability may work on improving the quality of gametes/embryos obtained from poor prognosis patients. This review would discuss the progressive evolution of embryo culture media based on studies on pre-implantation embryo physiology and lastly will hypothesize the future of this technology.
Keywords: Gametes; Embryo; Preimplantation; Sequential Media; Mono culture Media.